Study of Apelin Serum Levels in patients with Hepatitis C virus Chronic Liver Disease. - Ata, Moustafa Bakrey; Korah, Tarek El-Mahdy; El-Azab, Gasser Ibrahim; El-Fatah Badr, Eman Abd; Amin El-Zorkany, Khaled Mohamed (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Objective: The aim was to study the apelin serum levels and assessment of insulin resistance role in chronic liver diseased patients. Background: Apelin is involved in many physiological and pathological function in human, it is thought to increase liver fibrosis progression with the aid of insulin resistance. There is a significant association of insulin resistance and apelin level and liver progression. Materials and methods: This study was carried at Internal Medicine Department and National Liver Institute, Menoufia University Hospitals, from the period of January 2014 to October 2014. Subjects were classified into 5 groups each group contained 15 subjects: Group (I) served as healthy control of matched sex and age, Group (II) had liver steatosis without HCV infection, Group (III) had HCV-related liver steatosis, Group (IV) had HCV-related liver fibrosis and Group (V) had HCV-related liver cirrhosis. Results: Serum apelin level was elevated in liver steatosis, fibrosis and it was significantly higher in cirrhotic patients. Insulin resistance correlate positively with serum apelin and liver disease progression. Conclusion: Serum apelin is significantly higher in patients with HCV-liver cirrhosis compared to HCV-related liver fibrosis and steatosis that say, apelin plays a role in progression of liver disease and inhibition of the apelinergic system could offer new therapeutic opportunities against liver complication. A strong relation between insulin resistance and apelin on one side and other side between insulin resistance and liver fibrosis progression.